USING SERVICE-LEARNING IN GRADUATE EDUCATION TO ENGAGE STUDENTS AND THE COMMUNITY: OPPORTUNITIES AND CHALLENGES. (11th November 2018) - Watson, W; Stelle, C
Abstract: While gerontology has a long history of incorporating service-learning and community engagement (SLCE) into core courses, service-learning has had less utilization in graduate education. This presentation will discuss projects that have been developed to create opportunities for students to master content and to engage with older adults and the broader community. These SLCE projects include a project asking older adults to reflect on the concept of age-friendly communities. This project allowed students to learn about conducting research within a research methods course and to apply this knowledge in participatory action research, focusing on the goal of developing communities that are supportive for older adults. A second project focused on students working with older adults to learn about successful aging. For this project, students developed an interview to ascertain what successful aging was from the standpoint of the older adult. The last SLCE project focused on having students participate in a community-based seminar on aging in place and environmental design through a collaboration with the university's Optimal Aging Institute. The service-learning component consisted of students working on home safety and universal design checklists with seminar participants, allowing students to take what they learned about environmental design and work with community-residing older adults to provide for a home that was conducive to aging in place safely. The purpose of this presentation is to describe the development, implementation, analysis, and dissemination of these SLCE projects as mechanisms of graduate education and to describe the opportunities and challenges of SLCE within graduate education.